Upaya Meningkatkan Aktivitas Siswa dalam Pembelajaran Matematika Melalui Pendekatan Cooperatif Learning di Kelas VI SD Negeri 23 Bukik Apik - Isnaini (Warta Pendidikan | e-Journal, 2022)
This research was purposed to improving the student activity by aproach Cooperative Learning in Mathemetic lessons. This research is the action class research that has three sikluses . hypotesis action from this research is cooperative learning approach that got to improve the student activity in doing mathemetic question exercises. The subject of this research is the sixth class of SDN 23 Bukik Apik,Kecamatan Baso,at 2019, it consist of thirty one Students. The instrument of Data Collective that used was An observation wide activity and the result of study test. To get the data was needed the compiler thing data such as, observation wide activitiy of student and the result of student test,and after that ,it wiil be analised. According to data analised result ,it will be meet some of important things likes, 1) it would be improvement of positif activity student by cooperative learning lesson,it is 45,6 % for the fiirst siklus tobe 66,2 % for the second siklus and the last tobe 84,8% for the third siklus.2) it would be negative degradation student activity by cooperative learning lesson.it’s 18,25%for the firts siklus to be 7,25 % foor the second siklus, and the last 3,5% for the third siklus 3) it would be improvement of student study result by aproach cooperative learning. For the first mean skor siklus is 7,35 and the third siklus is 8,03.